2009
DOI: 10.1111/j.1949-8594.2009.tb17951.x
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and Science Integration: Models and Characterizations

Abstract: The squeeze on instructional time and other factors increasingly leads educators to consider mathematics and science integration in an effort to be more efficient and effective. Unfortunately, the need for common understandings for what it means to integrate these disciplines, as well as the need for improving disciplinary knowledge, appears to continue to be significant obstacles to an integrated approach to instruction. In this study we report the results of a survey containing six instructional scenarios ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 16 publications
(19 reference statements)
1
51
0
4
Order By: Relevance
“…The benefits to be gained from such integration have been variously documented, together with the challenges faced. Studies have indicated that students become better problem solvers, display more positive and motivated learning, and improve in their mathematics and science achievements (e.g., Furner and Kumar 2007a;Stinson et al 2009). Specifically, through the integration of engineering, students should become more aware of its role and presence in society and be able to apply engineering design processes to the solution of real-world problems (e.g., National Academy of Engineering and National Research Council NAE and NRC 2009a).…”
Section: Stem Integration In the School Curriculummentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits to be gained from such integration have been variously documented, together with the challenges faced. Studies have indicated that students become better problem solvers, display more positive and motivated learning, and improve in their mathematics and science achievements (e.g., Furner and Kumar 2007a;Stinson et al 2009). Specifically, through the integration of engineering, students should become more aware of its role and presence in society and be able to apply engineering design processes to the solution of real-world problems (e.g., National Academy of Engineering and National Research Council NAE and NRC 2009a).…”
Section: Stem Integration In the School Curriculummentioning
confidence: 99%
“…One of the challenges facing researchers is how to overcome obstacles to effective STEM integration including the lack of a unified and explicit understanding of what this entails, together with inadequate knowledge of multidisciplinary content many teachers experience (Moore et al 2014a;Stinson et al 2009). It is beyond the scope of this study to investigate STEM integration more broadly; rather, the present study represents just one approach to such integration through introducing young students to meaningful engineering-based problems that draw upon their curriculum in mathematics, science, and technology and engage them in the processes of engineering design.…”
Section: Stem Integration In the School Curriculummentioning
confidence: 99%
“…In another project, middle school teachers of science and mathematics understandings of integration were surveyed via reflection on various presented scenarios, and description of their own attempts at integration (Stinson et al 2009). Differences were identified in their characterisations of integration, and content knowledge was perceived as a barrier to integration.…”
Section: Large-scale Empirical Studiesmentioning
confidence: 99%
“…Over the past the past twenty years, scholarly journals, and articles in various STEM areas published many articles devoted to areas such as integrated instruction, interdisciplinary approaches, fused, trans disciplinary, and thematic teaching (e.g., Berlin & White, 1995;Brazee & Capelluti, 1995, Stinson, Harkness, Meyer, & Stallworth, 2009). Shoemaker (1991) suggested that there are "an equal number of terms to describe the various ways integrated instruction might be approached" (p. 793).…”
Section: What Is Integrated Stem Education?mentioning
confidence: 99%